Pembelajaran Sastra dengan Perspektif Dekonstruksi untuk Meningkatkan Kemampuan Berpikir Kritis di Universitas - Rahma, Salsabila Shofia; Tara, Silmi Nur Azizah; Safitri, Ruli Nur (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The ability to think critically is one of the skills that students must have in facing the challenges of the 21st century. One of the alternatives in learning literature that emphasizes critical thinking is through the perspective of deconstruction. This article tries to propose ideas about the urgency of reconstructing literature learning based on the analysis of Derrida's deconstruction theory and explores the potential of the deconstruction approach in training students' critical thinking skills in learning literary criticism. Through in-depth analysis of literary works, this research aims to identify how deconstruction can help students identify and challenge the assumptions underlying the text, as well as build more inclusive and diverse interpretations. This research uses a qualitative method with a literature study approach in examining the novel as the object of study in the perspective of literary deconstruction. The results show that there are 3 stages of deconstruction reading, namely (1) careful reading, (2) reconstruction, and (3) deconstruction so as to find the invention at the end of the analysis. Hopefully, the results of this study can make a significant contribution to the development of curriculum and teaching methods of literary criticism that are more effective, relevant, and in line with the development of contemporary literary studies.